High Quality Intelligent Database Driven Microcontroller Based Heartbeat Monitoring System - Babu Loganathan, ganesh; E.Mohan, Dr. (International Journal of Engineering and Technology, 2026)
This paper for a microcontroller primarily based hart beat observance system. It offers the advantage of mobility over sequence recording systems. The guts rate is keep within the info for analysis. This paper explains however a single-chip microcontroller is additionally accustomed analyse heart beat rate signals in quantity. To boot, it permits doctors to induce the hart beat rate file of the patient. It should even be used to management patients or athletic person over Associate in nursing extended quantity. This technique reads and stores the hart beat rate signals repetitively in amount. The hardware and code vogue unit of measurement oriented towards microcontroller-based system, so minimizing the size. The mandatory feature of this paper is that the employment of zero crossing formula to calculate rate. It then processes on fundamental measure the data to figure out some heart diseases.
Keywords: Non-Invasive Blood Pressure; Heart rate; bits per minute; GSM and GPS